Suppression of beta 2 adrenergic receptor actions prevent UVB mediated cutaneous squamous cell tumorigenesis through inhibition of VEGF‐A induced angiogenesis. Issue 3 (22nd January 2021) - Lu, Kai; Bhat, Madhavi; Peters, Sara; Mitra, Rita; Oberyszyn, Tatiana; Basu, Sujit
Abstract: Although beta 2 adrenergic receptors (β2 ADR) are present in the keratinocytes, their role in cutaneous squamous cell tumorigenesis needs to be ascertained. For the first time, we report here that selective β2 ADR antagonists by inhibiting β2 ADR actions significantly retarded the progression of ultraviolet B (UVB) induced premalignant cutaneous squamous cell lesions. These antagonists acted by inhibiting vascular endothelial growth factor‐A (VEGF) mediated angiogenesis to prevent UVB radiation‐induced squamous cell carcinoma of the skin.